Analytical formulae for the elastic-plastic analysis of I-Shaped cross-sections bent over their weak axis - Baptista, A. M. (2010)
This paper presents an analytical elastic-plastic model to study steel I-shaped cross-sections bent over their weak axis. The basic variables are the cross-section global deformations from which it is possible to evaluate the internal loads and the cross-section stiffness terms by means of a set of simple mathematical relationships. The model allows the yield spreading across the sections as well as the effects of the strain hardening and global deformations interaction to be taken into account on the non-linear cross-section behaviour in the elastic-plastic domain. The section failure by excessive deformation of its most strained fibres may also be directly controlled by these expressions. This model represents an efficient, simple and accurate alternative to the models based on the analysis of the cross-section by means of numerical integration over the cross-section divided into elementary fibres or layers.